2012
DOI: 10.1371/journal.pone.0034853
|View full text |Cite
|
Sign up to set email alerts
|

Who Underreports Smoking on Birth Records: A Monte Carlo Predictive Model with Validation

Abstract: BackgroundResearch has shown that self-reports of smoking during pregnancy may underestimate true prevalence. However, little is known about which populations have higher rates of underreporting. Availability of more accurate measures of smoking during pregnancy could greatly enhance the usefulness of existing studies on the effects of maternal smoking offspring, especially in those populations where underreporting may lead to underestimation of the impact of smoking during pregnancy.Methods and FindingsIn thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Third, smoking can be underreported on birth certificates and thus, the results of the sensitivity analysis may not have fully captured the extent to which maternal smoking underlies the relationship between maternal nativity and abdominal wall defects. 39 Fourth, we did not examine maternal alcohol usage because the correlation between birth certificate data and actual maternal alcohol use is very weak. 40 Fifth, there is heterogeneity within Mexican Americans with respect to region of origin in Mexico, US migration patterns, and region of residence in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Third, smoking can be underreported on birth certificates and thus, the results of the sensitivity analysis may not have fully captured the extent to which maternal smoking underlies the relationship between maternal nativity and abdominal wall defects. 39 Fourth, we did not examine maternal alcohol usage because the correlation between birth certificate data and actual maternal alcohol use is very weak. 40 Fifth, there is heterogeneity within Mexican Americans with respect to region of origin in Mexico, US migration patterns, and region of residence in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that linked data differentially increased the ascertainment of smokers, not only in women who are at higher risk of adverse outcomes (older age, multi-fetus pregnancy, diabetes, hypertension) but also in women who are known to underreport their smoking status (older age, married, immigrants from non-English speaking countries, and high socioeconomic status). 23,26,27 Factors contributing to voluntary disclosure of smoking among 51 In addition, it is also important that linking the records has resulted in a greater detection of smokers among women who gave birth in private and rural hospitals, given existing evidence that the data recording in these hospitals is less likely to be complete than in public or urban hospitals. 17,52 Comparing the two enhanced algorithms, it was found that additional information from antenatal admissions provided little enhanced benefit.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Underreporting of smoking status, however, may bias the findings of research relying on a single source of routine data. [22][23][24][25][26] Studies conducted in Australia and elsewhere using biochemical testing to validate self-reporting of smoking status have reported that between 6% and 39% of smoking women do not disclose their smoking status. [27][28][29][30][31] Greater levels of non-disclosure are found in women who are older, married and have higher socioeconomic status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Likewise, Land et al (2014) examined predictors of smoking status under-reporting during pregnancy and used a predictive model integrating socio-demographic correlates to produce more accurate smoking prevalence estimates among pregnant women (in their case, under-reporting lowered self-report estimates by values ranging from 1.1 to 1.9 percentage points). 15 …”
Section: Discussionmentioning
confidence: 99%